Economic Globalization: Management Strategy and E-Commerce Trends at the Retail Business in Medan City (Indomaret): Globalisasi Ekonomi: Strategi Manajemen dan Tren E-Commerce pada Bisnis Ritel di Kota Medan (Indomaret) - Rizka Oktaviana; Sri Rezeki (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2025)
This study aims to examine the influence of management strategy and e-commerce trends on economic globalization at the retail businesses in Medan City. The research approach uses a quantitative method with path analysis based on Partial Least Squares Structural Equation Modeling operated through SmartPLS software. The respondents consisted of Indomaret consumers in various branches of Medan City who were selected by incidental sampling technique, where each consumer who was met by chance and met the criteria became the source of the data. The research instrument included a structured questionnaire with indicators for the three latent variables. The results of the analysis show that management strategies have a significant positive influence with moderate strength, while e-commerce trends display a higher magnitude positive influence. Simultaneously, the two constructs are able to explain about two-thirds of the variability in economic globalization. These findings confirm the importance of the synergy of adaptive managerial frameworks and digital capabilities in driving the integration of local markets into global economic networks. The practical implications of the research include recommendations for the implementation of agile iteration-based management transformation protocols and the improvement of omnichannel capabilities to strengthen competitiveness in the digital era.